Biogea - Serres, Michel (Book collections on Project MUSE., 2012)
"Biogea is a mixture of poetry, philosophy, science, and biography exemplary of the style that has made Michel Serres one of the most extraordinary thinkers of his age. His philosophical and poetic inquiry sings in praise of earth and life, what he names singularly as Biogea."--Amazon.com.